2015
DOI: 10.1111/1751-2980.12256
|View full text |Cite
|
Sign up to set email alerts
|

The effect of position on esophageal structure and function determined with solid‐state high‐resolution manometry

Abstract: Body position exerts a greater influence on the LES than on the UES. Thus, it is necessary to establish normal values for the LES basal pressure and residual pressure in different positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
(54 reference statements)
2
12
2
Order By: Relevance
“…In addition, although HRM can be performed in both supine and sitting positions, HRM was conducted only in an upright sitting position in the present study. Zhang et al [ 34 ] reported that there was no difference in UES basal pressure between sitting and supine position measured using HRM. However, to our knowledge, there has been no previous study that evaluated the effect of posture on VP and TB pressure using HRM.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although HRM can be performed in both supine and sitting positions, HRM was conducted only in an upright sitting position in the present study. Zhang et al [ 34 ] reported that there was no difference in UES basal pressure between sitting and supine position measured using HRM. However, to our knowledge, there has been no previous study that evaluated the effect of posture on VP and TB pressure using HRM.…”
Section: Discussionmentioning
confidence: 99%
“…One thousand seven hundred fourteen patients were included, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] of whom 1284 were symptomatic and 430 asymptomatic individuals. The sequence of the position assumed during HRM was described in almost all studies.…”
Section: High-resolution Manometry Protocolsmentioning
confidence: 99%
“…Some authors referred that the exam was started in the supine position and the subsequent series of swallows was performed in the sitting/upright position; 12,14,15,18,19,24 other referred the opposite. 16,20,22,23 both to the upright or supine position in the studies by Zhang et al 17,21 and Misselwitz et al 26 Only 5 studies 14,16,17,19,24 reported the inclination assumed by the patient during the exam: between 0° and 20° for the supine position and between 75° and 90° for the upright/sitting position. Every study included at least 5 water bolus swallows per set for each position.…”
Section: High-resolution Manometry Protocolsmentioning
confidence: 99%
See 2 more Smart Citations